1993
DOI: 10.1002/jcb.240520208
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐Dihydroxyvitamin D3 increases type 1 interleukin‐1 receptor expression in a murine T cell line

Abstract: The biologically active metabolite of vitamin D3, 1,25 (OH)2 D3, exerts important immunoregulatory effects in addition to being a central mediator of calcium/phosphate metabolism. Utilizing an interleukin 1 responsive murine T cell line and 125I-interleukin 1 alpha, we show that 1,25 (OH)2 D3 (5,50 nM) enhanced 125I-interleukin 1 alpha binding up to almost 2-fold over control. This 1,25 (OH)2 D3 effect occurred in a dose-dependent manner and was detectable after 24 h but not before 7 h of culture. Scatchard an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The vitamin D 3 upregulated protein 1 (VDUP1), which is expressed in a 1α,25(OH) 2 D 3 -dependent manner, has been found to inhibit the activity of the IL-3 receptor promoter (Han et al, 2003). On the other hand, IL-1 and IL-4 receptor densities seem to be upregulated by 1α,25(OH) 2 D 3 on a murine T-cell line and a murine osteoblast cell line, respectively (Lacey et al, 1993a,b). Furthermore, downregulated IL-22 mRNA and protein levels have been detected in cultured epidermis tissue treated with calcipotriol, a vitamin D analog (Moniaga et al, 2013).…”
Section: α25(oh)2d3 As Regulator Of Cytokine Gene Expression Protementioning
confidence: 99%
“…The vitamin D 3 upregulated protein 1 (VDUP1), which is expressed in a 1α,25(OH) 2 D 3 -dependent manner, has been found to inhibit the activity of the IL-3 receptor promoter (Han et al, 2003). On the other hand, IL-1 and IL-4 receptor densities seem to be upregulated by 1α,25(OH) 2 D 3 on a murine T-cell line and a murine osteoblast cell line, respectively (Lacey et al, 1993a,b). Furthermore, downregulated IL-22 mRNA and protein levels have been detected in cultured epidermis tissue treated with calcipotriol, a vitamin D analog (Moniaga et al, 2013).…”
Section: α25(oh)2d3 As Regulator Of Cytokine Gene Expression Protementioning
confidence: 99%
“…In fact, vitamin D3 has: been shown to have stimulatory effects on various T cell functions including secretion and responsiveness to various cytokines [38][39][40], although immunoinhibitory effects by vitamin D3 have also been reported [40]. Although we have shown that the enhancement in T cell function coincides with vitamin D3 blockage of the capacity of the tumor to maintain myelopoiesis-associated suppressor activity, the possibility that vitamin D3 may have direct immunostimulatory effects on T cell function cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%